Impact Of The National Program For The City Without Slums (Kotaku) On The Economic Aspect Of The Community Of Somba Opu District, Gowa Regency - Ahmad Aidil Ardiansyah Ahmad (Pustaka Digital Indonesia, 2021)
The purpose of the study was to determine the impact of the National Program for Cities without Slums (KOTAKU) on the economic aspects of the people of Somba Opu sub-district, Gowa Regency. This type of research is qualitative research. The results of this data were taken directly at the secretariat of the Kotaku Coordinator and the slum community in 14 Kelurahan in Somba Opu District. The results showed that the program implemented in Somba Opu District, Gowa Regency experienced the fastest reduction in slum area through improving the quality of the environment by building residential infrastructure. The development is expected to bring positive changes to the economic aspects of the community because this aspect is one of the indirect causes of the emergence of slum settlements. The results of this study are the KOTAKU program has a positive impact from the economic aspect, namely increasing income and increasing community employment. Income is the impact that benefits the most when implementing the development of the KOTAKU Program. Utilization of infrastructure development and economic activities from the KOTAKU Program needs to be increased to provide more impact on the economic aspects of the community.